2020
DOI: 10.3390/agronomy10101601
|View full text |Cite
|
Sign up to set email alerts
|

Warming Reduces Net Carbon Gain and Productivity in Medicago sativa L. and Festuca arundinacea

Abstract: High temperature stress imposes constraints on the productivity of agricultural systems, such as pastures, and predicted increases in global temperatures are set to exacerbate these limitations. Here, we sought to understand the impact of warmer growth temperature on gas exchange and net primary productivity for two widely cultivated pasture species. We grew a C3 legume, Medicago sativa (lucerne), and a C3 grass, Festuca arundinacea Schreb (tall fescue), in a climate-controlled facility exposed to two temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 102 publications
1
11
0
Order By: Relevance
“…At the leaf-level, we found no significant change in A leaf in plants grown at elevated relative to ambient, temperature, suggesting that temperatures in this study were at or near optimum. This is supported by a reported temperature optimum of 28-29°C for net leaf photosynthesis in F. arundiancea (Jacob et al, 2020). Furthermore, increased plant respiration in a warmer climate is predicted to drive many ecosystems from being C sinks to sources (Feng et al, 2018;Luo, 2007), although this response was not observed for dark R leaf in our study.…”
Section: Does Warming Alter C Allocation In Perennial Grass?supporting
confidence: 76%
See 2 more Smart Citations
“…At the leaf-level, we found no significant change in A leaf in plants grown at elevated relative to ambient, temperature, suggesting that temperatures in this study were at or near optimum. This is supported by a reported temperature optimum of 28-29°C for net leaf photosynthesis in F. arundiancea (Jacob et al, 2020). Furthermore, increased plant respiration in a warmer climate is predicted to drive many ecosystems from being C sinks to sources (Feng et al, 2018;Luo, 2007), although this response was not observed for dark R leaf in our study.…”
Section: Does Warming Alter C Allocation In Perennial Grass?supporting
confidence: 76%
“…The leaf physiological responses to the combined drought and warming treatment, such as an increase in the dark R leaf and reduction in Ψ MD and A leaf , were mainly driven by drought. Negative effects of temperature on leaf physiology were not apparent in our study, potentially because it was at or near the thermal optimum for growth and productivity (Hill et al, 1985; Jacob et al, 2020). Garcia‐Forner et al (2016) also found that the effect of combined drought and heat treatment on hydraulics and gas exchange in trees was not synergistic.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Festuca and Medicago are widely planted across Europe, North and South America, Australasia and Africa ( Gibson and Newman, 2001 ; Ghaleb et al, 2021 ), contributing to the pasture feed-base that underpins global livestock production. These temperate species have optimum temperatures for photosynthesis in the region of 20–29 o C ( Festuca; Sasaki et al, 2002 ; Sinclair et al, 2007 ; Jacob et al, 2020 and 15–30 o C ( Medicago; Al-hamdani and Todd, 1990 ; Jacob et al, 2020 ). Whilst winter warming is, therefore, likely to stimulate gross photosynthetic rates, spring temperatures were regularly above these thresholds, especially in the later part of the season where daily maxima of over 45 o C were recorded in warmed plots.…”
Section: Discussionmentioning
confidence: 99%
“…Festuca and Medicago are widely planted across Europe, North and South America, Australasia and Africa (Gibson and Newman, 2001;Ghaleb et al, 2021), contributing to the pasture feed-base that underpins global livestock production. These temperate species have optimum temperatures for photosynthesis in the region of 20-29 o C (Festuca; (Sasaki et al, 2002;Sinclair et al, 2007;Jacob et al, 2020) and 15-30 o C (Medicago;Al-hamdani and Todd, 1990;Jacob et al, 2020). Whilst winter warming is, therefore, likely to stimulate gross photosynthetic rates, spring temperatures were regularly above these thresholds, especially in the later part of the season where daily maxima of over 45 o C were recorded in warmed plots.…”
Section: Plant Responses To Warming and Drought  Warming Interactionsmentioning
confidence: 99%